Using three-dimensional laser scanning for monitoring a long-span arch bridge launch. Issue 3 (8th May 2019) - Chao, Min; Chiu, Hao-Jan; Lu, Chih-Wei; Jeng, Chyuan-Hwan
Abstract : A 140 m span arch bridge was launched across a watercourse in Taiwan using a special hydraulic crawler system. Temporary structural and geotechnical facilities included four launching tracks and their supporting foundations and structures. Laser scanning was used to capture three-dimensional geometric information of the launching facilities before, during and after launching. The captured spatial data were then used to analyse deformations in the facilities under launch loading. This paper describes the methodology, results and performance of the laser scanning approach. The results are compared with those obtained from other monitoring approaches, revealing that laser scanning provides a satisfactory performance.